Zwischen Nord- und Süddeutschland: Die Überwindung räumlicher Distanzen bei der Arbeitsmarktmobilität - Michael Windzio (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2004)
– This paper analysing the regional mobility of labour uses the IAB regional sample (west) to examine changes of job involving a move from north to south. From an action-theory point of view, attention is paid not only to the people's individual factors such as level of education/training, income or unemployment, but also in particular the spatial context conditions which have an influence on the rates of mobility between the north and the south. The focus of attention is both the level of regional unemployment and the distance from the particular boundary between the north and the south. The findings of a time-discrete rate model, which takes into account the clustering of observations within the contexts, show among other things that the rate of mobility from north to south decreases as the distance increases. However, this negative effect is counteracted above all by a higher level of education/training, and only to a very small extent does the willingness to overcome distances between north and south increase due to long-term unemployment. On the whole it becomes clear that regional labour-market mobility over greater distances seems to be a costly investment which is afforded principally by people who have the appropriate material and education-related resources. Especially for northern Germany's low-skilled people, long-term unemployed and people in poorly-paid jobs, who represent the actual (potential) problem cases on the labour market, moving to the far better labour markets of southern Germany is unlikely.
Keywords: 330; Arbeitslose; Mobilitätsbereitschaft; Arbeitskräftemobilität; regionale Mobilität - Determinanten; IAB-Regionalstichprobe; Norddeutschland; Süddeutschland; Westdeutschland; Bundesrepublik Deutschland